Hambatan Implementasi Coretax dalam Reformasi Birokrasi Perpajakan Indonesia - Khairunisa Putri; Salma Zulfa Nur Habibah; Aulia Putri Maharani; David Jonathan Kristian Simanjuntak; Fairuz Arkan Fatihah; Aqil Teguh Fathani; Jerry Indrawan (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
Indonesia's tax bureaucracy reform has entered a critical phase with the launch of the Core Tax Administration System (Coretax) by the Directorate General of Taxes (DGT) on December 31, 2024, formally implemented in January 2025. Designed to integrate all taxation processes into a single digital platform, Coretax represents the most ambitious digital transformation in Indonesian tax administration history. However, its early implementation revealed significant technical and institutional obstacles that undermined its intended efficiency gains. This study aims to analyze the barriers to Coretax implementation within the framework of Indonesia's tax bureaucracy reform. Using a qualitative case study method with semi-structured interviews and documentation techniques, data were collected from DGT officials and analyzed through George C. Edwards III's policy implementation theory, encompassing four variables: communication, resources, disposition, and bureaucratic structure. The findings reveal that implementation barriers are multidimensional: communication gaps stem from uneven digital literacy among users; resource readiness claims do not fully reflect real field capacities; institutional framing obscures variation in staff adaptation; and bureaucratic fragmentation impedes coordinated responses across units. These four variables operate simultaneously and reinforce one another, producing systemic institutional dysfunction that hinders optimal Coretax implementation